PERSONALIZED TEXT-TO-IMAGE DIFFUSION MODEL - Ruiz Gutierrez, Nataniel; Jampani, Varun; Aberman, Kfir; Li, Yuanzhen; Pritch Knaan, Yael; Rubinstein, Michael (2024)
Methods, systems, and apparatus, including computer programs encoded on computer storage media, for training a text-to-image model so that the text-to-image model generates images that each depict a variable instance of an object class when the object class without the unique identifier is provided as a text input, and that generates images that each depict a same subject instance of the object class when the unique identifier is provided as the text input.